Intellectual Property Rights in Tourism Management in Cirebon - Surono, Surono; Bastoni, Bastoni; Prawira Triutama, Oqke; Khairune Nisa, An Nuur (Ann Publisher, 2024)
Tourism requires risk management for its sustainability. With risk management, we can prevent the peril that causes losses, especially in tourism. Looking at the current conditions, the rampant piracy cases of tourism products certainly require a strategy as a preventive measure. Especially with the development of society 5.0, of course, it makes the hazard of these risks even more significant. Moreover, it gives new exposure to tourism management. The Ministry of Tourism and Creative Economy makes a strategy to protect tourism products by collaborating with the Director General of IPR of the Ministry of Law and Human Rights and training tourism actors to carry out legal protection by owning Intellectual Property Rights (IPR). The IPR was registered with the Directorate General of Intellectual Property Rights of the Ministry of Human Rights. Tourism management in Indonesia requires instilling in the community and local tourism entrepreneurs an understanding of the importance of IPR ownership. The Ministry of Tourism and Creative Economy is intensively organizing socialization of the importance of IPR to tourism actors, which will be held in December 2021 in various cities to prevent theft of culture and tourism products to realize sustainable tourism. One of them is in Cirebon City; at the end of December, an Intellectual Property Class will contain education about IPR.